Trend Minat Mahasiswa Universitas dr. Soetomo dalam Berbelanja secara Online di Tokopedia (Jurnal Kajian Media, 2017)
This study aims to find out what kind of tokopedia marketing model to attract students of Dr.Soetomo University, Surabaya, this study discusses online shop in tokopedia and online shopping patterns, and follow the modern era, a research approach that uses social change theory and consumption approach qualitative with descriptive method, data collecting technique is done by documentation, in-depth interview, observation, and search of field data. Informant researchers as many as 6 people taken from the most important person from each faculty of the university. Soetomo Surabaya and I take the average chairman of BEM and BEM representatives of each faculty and also actively follow the organization in the University of Dr Soetomo Surabaya.tujuan this research To find out how and what the marketing of tokopedia that can make the students of Universitas Dr. Soetomo can be interested in tokopedia. Based on what I studied from their students interested in tokopedia compared with other online shop, Tokopedia began to develop the transaction model that is by doing cooperation with merchant merchants like alfamart and indomart and many more. In addition to the many promos made tokopedia and merchant merchants are making their own advantages for the merchant entrepreneurs who have worked with tokopedia. Another reason that is also expressed by users of tokopedia especially university students. Soetomo Surabaya. According to some of them consider tokopedia as the only pioneer online shop. In addition, according to them tokopedia still put quality of the goods they sell. The conclusion of this study differences in traditional shopping patterns through barter and modern shopping patterns are very much different due to the development of the era and highly sophisticated technology in this era of the year, the increase in technology will make the people happy with how they shop very easy and affordable.Keywords: shopping needed, online shopping, tokopedia